(untitled) (Global Journal of Management and Business Research, 2022)
The behaviour construct mainly deals with consumer choice related to a service or product The last construct the Intention behaviour related to an intention to purchase a product also reflects consumers preference Peslak Ceccucci and Sendall 2012 found that both attitude toward social networking and subjective norm is associated with intention to use social networking The authors highlighted two key deterministic aspects of social networking mainly the effect of social networks on demographics and the main benefit of cost savings One of the shortcomings of only considering demographics is that social networking may target a specific target market mainly the young population that frequently uses social media